2018
DOI: 10.5005/jp-journals-10047-0058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Bond Strength and Mode of Failure of Glass Fibre Posts Luted using Two Different Adhesives: An In Vitro Analysis

Abstract: Aim:The aim of this study is to assess the bond strength and the mode of failure of a glass fibre-post luted using two different adhesives. Materials and methods:Fourty human permanent maxillary central incisors were decoronated, endodontically treated, divided into two groups (n = 20), after post space preparation; group I: clear post RO (Dispodent) and Variolink II (Ivoclar Vivadent); group II: clear post RO (Dispodent) and Multilink N(Ivoclar Vivadent). The roots were sectioned to a thickness of 2 ± 0.5. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A recent study by Ishwarya et al compared the bond strength and mode of failure of glass fiber posts luted using two different adhesives and concluded that superior bond strength was seen in two-step etch and rinse adhesives rather than self-etch adhesives due to enhanced resin cement penetration into the dentinal substrate [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Ishwarya et al compared the bond strength and mode of failure of glass fiber posts luted using two different adhesives and concluded that superior bond strength was seen in two-step etch and rinse adhesives rather than self-etch adhesives due to enhanced resin cement penetration into the dentinal substrate [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The type of failure was assessed using Stereomicroscopy (10x). Failures were classified as:  Type 1: Adhesive failure between post and luting cement  Type 2: Adhesive failure between dentin and luting cement  Type 3: Cohesive failure of post system  Type 4: Cohesive failure of luting cement  Type 5: Mixed type; combination of any two of the above-mentioned types [6] .…”
Section: Fracture Testing Proceduresmentioning
confidence: 99%